2022
DOI: 10.1007/s10639-022-10943-7
|View full text |Cite
|
Sign up to set email alerts
|

Looking at MOOC discussion data to uncover the relationship between discussion pacings, learners’ cognitive presence and learning achievements

Abstract: The MOOCs (Massive Open Online Courses) forum carries rich discussion data that contains multi-level cognition-related behavior patterns, which brings the potential for an in-depth investigation into the development trend of the group and individual cognitive presence in discourse interaction. This paper describes a study conducted in the context of an introductory astronomy course on the Chinese MOOCs platform, examining the relationship between discussion pacings (i.e., instructor-paced or learner-paced disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Furthermore, technology-assisted learning also enables a learner to acquire supportive learning materials easily, which helps in making their prospective concepts clear and boosts their academic achievement. This finding reflects the findings of Liu et al (2022) , where learners reported a high level of cognitive understanding and learning achievements in the MOOC discussion forum. Thus, in order to enhance students’ learning achievements, it is considered worthwhile for teachers to frame inquiry-based and open discussion activities integrated with the learning materials.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, technology-assisted learning also enables a learner to acquire supportive learning materials easily, which helps in making their prospective concepts clear and boosts their academic achievement. This finding reflects the findings of Liu et al (2022) , where learners reported a high level of cognitive understanding and learning achievements in the MOOC discussion forum. Thus, in order to enhance students’ learning achievements, it is considered worthwhile for teachers to frame inquiry-based and open discussion activities integrated with the learning materials.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies also highlighted the significance of ICT-integrated instructional approaches in meeting the educational needs of the learners by increasing their thoughtfulness and keeping students motivated, which is viewed as a significant predictor of students’ educational growth ( Xu et al, 2021 ). Liu et al (2022) also identified that technology-integrated learning increases the cognitive understanding and learning achievements of students. In addition, ICT incorporated teaching-learning practices also enable learners to stay connected with their instructors and peers ( via various social media platforms), help students resolve their academic challenges and keep them participating actively in the learning activities ( Liu Z. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%
“…Although this approach is convenient and practical, it suffers the risk of overlooking connections between CP phases. Garrison (2016) and Liu et al (2022) suggested that CP does not always develop linearly. Instead, there can be constant interactions in the action‐deliberation and perception‐conception dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al ( 2022b ) explores the relationship between social interaction, cognitive processing and learning achievement in a MOOC discussion forum. Liu et al ( 2022c ) discusses the relationship between discussion pacing (i.e., instructor-paced or learner-paced discussion), cognitive presence, and learning achievements. Emotion experiences, cognitive presence or social interactions in discourses as highlighted by the works of (Liu et al, 2019 , 2022a , 2022b , 2022c ) provide some deeper and implicit features that have a definite impact on the learning achievement of the learner.…”
Section: Literature Reviewmentioning
confidence: 99%